Managing advanced prostate cancer in the Asia Pacific region: "Real‐world" application of Advanced Prostate Cancer Consensus Conference 2019 statements. Issue 6 (8th February 2022) - Chiong, Edmund; Murphy, Declan G.; Buchan, Nicholas C.; Chua, Melvin L. K.; Hakim, Lukman; Hamid, Agus Rizal; Hong, Sung K.; Horvath, Lisa G.; Kanesvaran, Ravi; Khochikar, Makarand; Letran, Jason; Lojanapiwat, Bannakij; et al.
Abstract: Aim: The second Asia‐Pacific Advanced Prostate Cancer Consensus Conference (APAC APCCC 2020) gathered insights into the real‐world application in the Asia‐Pacific (APAC) region of consensus statements from the 3rd Advanced Prostate Cancer Consensus Conference (APCCC 2019). Methods: The 4‐h our virtual meeting in October 2020 brought together 26 experts from 14 APAC countries to discuss APCCC 2019 recommendations. Presentations were prerecorded and viewed prior to the meeting. A postmeeting survey gathered views on current practice. Results: The meeting and survey highlighted several developments since APAC APCCC 2018. Increased access and use in the region of PSMA PET/CT imaging is providing additional diagnostic and staging information for advanced prostate cancer and influencing local and systemic therapy choices. Awareness of oligometastatic disease, although not clearly defined, is increasing. Novel androgen receptor pathway antagonists are expanding treatment options. Cost and access to contemporary treatments and technologies continue to be a significant factor influencing therapeutic decisions in the region. With treatment options increasing, multidisciplinary treatment planning, shared decision making, and informed choice remain critical. A discussion on the COVID‐19 pandemic highlighted challenges for diagnosis, treatment, and clinical trials and new service delivery models that will continue beyond the pandemic. Conclusion: APAC‐specific prostate cancer research and data are important to ensure that treatment guidelines and recommendations reflect local populations and resources. Facilitated approaches to collaboration across the region such as that achieved through APAC APCCC meetings continue to be a valuable mechanism to ensure the relevance of consensus guidelines within the region. Abstract : The second Asia‐Pacific Advanced Prostate Cancer Consensus Conference (APAC APCCC 2020) gathered insights into the real‐world application in the Asia‐Pacific (APAC) region of consensus statements from the 3rd Advanced Prostate Cancer Consensus Conference (APCCC 2019).